The Use of Innovative Methods of Oral Counting in Developing the Creative Abilities of a Future Primary School Teacher (Eurasian Journal of Learning and Academic Teaching, 2023)
In this article, formulas have been developed that allow you to verbally calculate the product of some natural numbers, and the importance of solving examples and problems using these formulas in preparing students with creative abilities is revealed.